Candida Isolates From Blood and Other Normally Sterile Foci From ICU Patients: Determination of Epidemiology, Antifungal Susceptibility Profile and Evaluation of Associated Risk Factors - Bo Wang; Xinlong He; Xinlong He; Feng Lu; Feng Lu; Yajuan Li; Yuerong Wang; Min Zhang; Ying Huang; Jinxing Xia (Frontiers Media S.A., 2021)
Background: The clinical diagnosis and therapy for ICU patients with invasive candidiasis are challenged by the changes of Candida community composition and antimicrobial resistance. The epidemiology and drug sensitivity of candidiasis in ICU as well as its risk factors and drug resistance mechanism were investigated.Methods: In the present study, 115 patients in ICU were recruited from June 2019 through July 2020. Among them, 83 Candida isolates were identified with MALDI-TOF mass spectrometry. The susceptibility to antifungals was measured by microdilution method. The molecular mechanisms of azole-resistant Candida tropicalis were explored by sequencing, and their outcomes were explicitly documented.Results:Candida glabrata and C. tropicalis were the predominant non-C. albicans Candida. The specimen sources were mainly urine, bronchoalveolar lavage fluid and blood. The age, length of hospitalization, tracheotomy, diabetes and concomitant bacterial infection were the main risk factors for candidiasis. The majority of Candida species exhibited susceptibility to antifungals. However, certain C. tropicalis were frequently resistant to azoles. The polymorphism of the ERG11 in C. tropicalis was likely associated with azole resistance.Conclusion: The multiple risk factors for candidiasis in ICU patients need to be considered. Certain C. tropicalis exhibit resistance to azoles likely due to the ERG11 gene polymorphism.